2007
DOI: 10.1097/01.ta.0000221667.32598.71
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Arteriovenous Extracorporeal Lung Assist and High-Frequency Oscillatory Ventilation in a Porcine Model of Lavage-Induced Acute Lung Injury: A Randomized Controlled Trial

Abstract: The combination of AV-ECLA and HFOV resulted in normocapnia and comparable Pao2, although a smaller ventilator pressure amplitude was applied. Long-term animal studies are needed to assess whether this approach results in further lung protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Lung-protective ventilation focuses on minimizing end-inspiratory stretch (using low tidal volumes) and minimizing derecruitment of the lung (application of PEEP). [ 4 , 7 ] However, even with protective mechanical ventilation recent studies have shown that acute lung injury continues to occur, with a paucity of effective therapeutic modalities. [ 8 ] Furthermore, several recent studies have documented that failure to recognize ARDS and implement timely lung protective strategies remains a widespread problem in intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…Lung-protective ventilation focuses on minimizing end-inspiratory stretch (using low tidal volumes) and minimizing derecruitment of the lung (application of PEEP). [ 4 , 7 ] However, even with protective mechanical ventilation recent studies have shown that acute lung injury continues to occur, with a paucity of effective therapeutic modalities. [ 8 ] Furthermore, several recent studies have documented that failure to recognize ARDS and implement timely lung protective strategies remains a widespread problem in intensive care units.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases the extent of the lung injury is rather severe, with a PaO 2 ! 40-60 mm Hg [23,24] , or just moderate with a PaO 2 ! 300 mm Hg [11,20] .…”
Section: Lav Modelmentioning
confidence: 99%
“…The use of animals in randomized trials has been effective in the study of endoscopic and surgical techniques. [18][19][20][21][22][23][24] There was focal necrosis detected at the margin of the transection in the ETDP group, without consequences in terms of clinical parameters and survival. The only pancreatic leak and postprocedure death occurred in a swine in the laparoscopic group.…”
Section: Discussionmentioning
confidence: 93%